Alcohol Use among Chinese Men Who Have Sex with Men: An Epidemiological Survey and Meta-Analysis. (11th March 2014) - Liu, Yu; Qian, Han-Zhu; Ruan, Yuhua; Yin, Lu; Ma, Juntao; Dahiya, Kapil; Fan, Wensheng; Shao, Yiming; Vermund, Sten H.
Abstract : The HIV/AIDS epidemic among Chinese men who have sex with men (MSM) has become a significant public health concern. Knowledge of alcohol consumption in this population is limited. In this study, 1, 155 Chinese MSM were surveyed to assess alcohol use and its correlates. A meta-analysis was also performed to aggregate pooled prevalence of current alcohol use. MSM who were unmarried (aOR: 1.87; 95% CI: 1.29–2.71) or unemployed/retired (aOR: 2.77; 95% CI: 1.73–4.45) were more likely to drink alcohol more than once per week. MSM who consumed alcohol more than once per week were more likely to use drug ( P < 0.01 ), have sex with women ( P < 0.01 ), have unprotected insertive ( P = 0.04 ) or receptive ( P = 0.03 ) anal sex with men, have more than 10 lifetime male sex partners ( P < 0.01 ), predominantly practice insertive anal sex ( P < 0.01 ), and trade sex for money ( P < 0.01 ) . Pooled overall alcohol use prevalence was 32%. Pooled prevalence for MSM who drank alcohol more than once per week and who drank alcohol before sex with male partners was 23%. Our findings provide the basis for further exploring the alcohol-HIV association and developing risk reduction interventions.